Twolined Spittlebugs in Turfgrass - D. E. Short; Eileen A. Buss; Larry Williams (EDIS)
Spittlebugs are present throughout the entire state, but they are more abundant in northern and northwestern Florida. They attack all turfgrass species, but centipedegrass is the most susceptible. Adults also feed on ornamental plants, especially hollies (Ilex cassine or I. opaca).  This document is ENY-334, one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date first printed October 1993. Revised: September 2005.